2015
DOI: 10.1590/2359-3997000000110
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influence on thyroid gland volume and thickness of thyroid isthmus: a twin study

Abstract: Objectives: Decreased thyroid volume has been related to increased prevalence of thyroid cancer. Subjects and methods: One hundred and fourteen Hungarian adult twin pairs (69 monozygotic, 45 dizygotic) with or without known thyroid disorders underwent thyroid ultrasound. Thickness of the thyroid isthmus was measured at the thickest portion of the gland in the midline using electronic calipers at the time of scanning. Volume of the thyroid lobe was computed according to the following formula: thyroid height*wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These comparisons were performed by comparing the lower and upper reference interval limits of this study's reference intervals with those of other studies previously reported in medical literature. Results indicate that for TSH, this study's gender independent lower reference interval limit is lower than that of Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al,20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population. However, the gender independent upper reference interval limit for TSH in this study is higher than that of gender independent upper reference interval limits for Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al, 20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population.…”
Section: Comparison Of Developed Reference Intervals For Thyroid Horm...mentioning
confidence: 58%
“…These comparisons were performed by comparing the lower and upper reference interval limits of this study's reference intervals with those of other studies previously reported in medical literature. Results indicate that for TSH, this study's gender independent lower reference interval limit is lower than that of Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al,20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population. However, the gender independent upper reference interval limit for TSH in this study is higher than that of gender independent upper reference interval limits for Darfur (Sudan) (Ali et al, 2018), British (Kratzsch et al, 2005) [12] , Australian (Hickman et al, 2017) [8] , American (Hollowell et al, 20) [9] , and Srpska Republic (Mirjani-Azaric et al, 2017) [15] populations, and gender dependent upper reference interval limit for Khartoum (Sudan) (Musa et al, 2018) [16] population.…”
Section: Comparison Of Developed Reference Intervals For Thyroid Horm...mentioning
confidence: 58%
“…Of course, the thyroid volume could not be entirely explained by anthropometric measurements. It is also determined by other factors, such as ethnicity, genetic background and environmental factors (smoking, nutrition, iodine intake) [ 10 , 11 , 12 , 13 ]. These could be the reasons for the variations of the results in different geographic areas [ 8 , 9 , 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a study from the Korea National Health and Nutrition Examination Surveys showed that factors related to thyroid function, such as thyroid-stimulating hormone (TSH) and free thyroxine (fT4), also present high heritability: the narrow-sense heritability for TSH is 54%, and that for free thyroxine (fT4) is 56%; the narrow-sense heritability is higher in females than that in males for TSH; and both TSH and fT4 show negative genetic correlations in females after adjusted for environmental effects [6]. In a twin study including 69 monozygotic and 45 dizygotic adult twin pairs, the environment-adjusted heritability of the thickness of thyroid isthmus and thyroid volume (left and right lobes) on thyroid cancer was 50% and 68-79%, respectively [7]. ese evidences reflect the high heritability of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%